Effect of sintering profile on the densification behaviour of forsterite ceramics /Tan Soon Sien - Tan, Soon Sien (2016)
Forsterite (Mg2SiO4) is well known to be potential biomedical implants due to its good mechanical properties compared to hydroxyapatite (HA). The fracture toughness of forsterite is exceptionally higher compared to hydroxyapatite (HA) and the values are close to a human femur bone. Several studies also suggested that the elements of forsterite such as Magnesium and Silicon are the key element in human body that helps promotes bone development as well as enhance osteoblast adhesion. In this study, the impact of prolong ball milling of forsterite (Mg2SiO4) during powder preparation and the sintering behavior of forsterite powder was prepared by mechanical activation and heat treatment. The green compacts were sintered by using two different sintering profiles. The first profile was based on conventional sintering (CS) profiles in which the powder compacts was sintered at the desired temperatures, holding for 2 hours and then cooled to room temperature. The synthesized forsterite samples were characterized by X-Ray diffraction, table-top scanning electron microscopy, water immersion test and Vickers hardness test to determine its phase characteristic, grain size, relative densities and its mechanical properties. It was found that a minimum ball milling time of 7 h was necessary to completely eliminate secondary phases from developing in the forsterite matrix after sintering at 1400ºC. The sintering study revealed that the sintered body prepared by CS profiles was effective in enhancing the fracture toughness when sintered at 1400ºC. However, the high sintering temperatures combined with long holding time promotes exaggerated grain growth. Alternatively, samples that are sintered below 1400ºC and have a lesser ball milling duration were found to be ineffective in preventing the formation of secondary phases in the sintered body. The second sintering profiles was based on a two-step sintering (TSS) profile in which the samples were initially sintered at a temperature T1 = 1400ºC for 6 minutes and then continued sintering the compacts at a lower temperature T2 (i.e. 750ºC, 850ºC and 950ºC) for 15 hours before cooling to room temperature. The TSS profile (T1 = 1400ºC, T2 = 950ºC) was found to be most beneficial in promoting densification and more importantly, to suppress grain coarsening of the forsterite body.